Association between the overall burden of comorbidity and Ct values among the older patients with Omicron infection: Mediated by inflammation - Wang, Meixia; Mi, Hongfei; Li, Na; Shi, Qingfeng; Sun, Wei; He, Tingjuan; Lin, Jiabing; Jin, Wenting; Gao, Xiaodong; Hu, Bijie; Su, Chenghao; Pan, Jue (Frontiers in Immunology, 2023)
Objectives To investigate the associations between the overall burden of comorbidity, inflammatory indicators in plasma and Ct values among the elderly with COVID-19. Methods We conducted a retrospective observational study. The results of each nucleic acid test of during hospitalization were obtained. Linear regression models assessed the associations between the overall burden of comorbidity, inflammatory indicators in plasma and Ct values among the elderly. A causal mediation analysis was performed to assess the mediation effects of inflammatory indicators on the association between the overall burden of comorbidity and Ct values. Results A total of 767 COVID-19 patients aged ≥ 60 years were included between April 2022 and May 2022. Patients with a high burden of comorbidity had significantly lower Ct values of the ORF gene than subjects with a low burden of comorbidity (median, 24.81 VS 26.58, P < 0.05). Linear regression models showed that a high burden of comorbidity was significantly associated with higher inflammatory responses, including white blood cell count, neutrophil count and C-reactive protein. Also, white blood cell count, neutrophil count, C-reactive protein and the overall burden of comorbidity assessed by age-adjusted Charlson comorbidity index were independent risk factors for the Ct values. A mediation analysis detected the mediation effect of white blood cells on the association between the burden of comorbidity and Ct values, with the indirect effect estimates of 0.381 (95% CI: 0.166, 0.632, P < 0.001). Similarly, the indirect effect of C-reactive protein was -0.307 (95% CI: -0.645, -0.064, P = 0.034). White blood cells and C-reactive protein significantly mediated the relationship between the burden of comorbidity and Ct values by 29.56% and 18.13% of the total effect size, respectively. Conclusions Inflammation mediated the association between the overall burden of comorbidity and Ct values among elderly with COVID-19, which suggests that combined immunomodulatory therapies could reduce the Ct values for such patients with a high burden of comorbidity.